CsPbBr3–Cs4PbBr6 composite nanocrystals for highly efficient pure green light emission. Issue 47 (25th November 2019) - He, Miao; Wang, Chunyun; Li, Jingzhou; Wu, Jiang; Zhang, Siwei; Kuo, Hao-Chung; Shao, Liyang; Zhao, Shichao; Zhang, Jinzhong; Kang, Feiyu; Wei, Guodan
Abstract : All-inorganic perovskite CsPbBr3 –Cs4 PbBr6 composite nanocrystals (NCs) were synthesized via a convenient solution process without inert gas protection and systematically studied as green phosphors for light emitting diode (LED) applications. Abstract : All-inorganic perovskite CsPbBr3 –Cs4 PbBr6 composite nanocrystals (NCs) were synthesized via a convenient solution process without inert gas protection and systematically studied as green phosphors for light emitting diode (LED) applications. While colloidal composite NCs emit green color with an emission peak at around 515 nm, their thin films on top of blue GaN chips exhibit a redshift of ∼15–20 nm due to subsequential aggregation in solid state. The Commission Internationale De I'eclairage (CIE) chromaticity coordinates of the green LEDs assembled by composite NCs reached (0.201, 0.746) with nearly 100% green ratio. Moreover, the pure green LED displayed a luminous efficiency of 45 lm W −1 under 10 mA driving current. The colloidal CsPbBr3 –Cs4 PbBr6 composite NCs have the photoluminescence quantum yield (PLQY) as high as 74%. The high PLQY originates from cubic CsPbBr3 NCs well passivated by the zero-dimensional Cs4 PbBr6 matrix, substantially suppressing the nonradiative recombination. The comparison between the green LEDs fabricated with pure and composite perovskites imply that the CsPbBr3 –Cs4 PbBr6 composites with higher quantum yield could be an effective way to get the brightness and the stability of pure green LEDs.